The impact of overeducation on wages of recent economic sciences graduates : An application to the case of the Universidad Nacional de Córdoba - De Santis, Mariana (2018)
Under the human capital theory, wages are determined by the worker productivity, which in its crudest form implies the return to education is not contingent on how the workers' skills are utilized in the labor market (Sloane, 2002). However, and after controlling for other differences, the empirical evidence has shown that workers with the same education can be paid differently. The literature has found young people are more likely to experience a mismatch between their formal education and the one required by the job. While there is not a consensus about the reasons for the mismatch, there is one about the consequences in terms of wages, overeducation means a penalty in terms of income. Our evidence shows that overeducated graduates of the FCE-UNC suffer a wage penalty when compared to those working in a job requiring a university degree. The results are robust to different specifications and to the use of alternative estimators. While the difference is not statistically significant, the penalty for those severely overeducated is larger than for those with a mild level of overeducation. To have working experience while studing at the university helps to reduce the cost of overeducation. The overall impact found for the whole sample appears to be driven by the impact of overeducation on female graduates. While for the case of overeducation we find statistically significant effects, the same is not the case for the level of horizontal match, either in terms of skills and knowledge.